2010
DOI: 10.1002/ccd.22563
|View full text |Cite
|
Sign up to set email alerts
|

“Device landing zone” calcification, assessed by MSCT, as a predictive factor for pacemaker implantation after TAVI

Abstract: Calcium amount in the CoreValve DLZ in combination with clinical data could predict the need for post TAVI PM implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(58 citation statements)
references
References 22 publications
2
49
2
5
Order By: Relevance
“…Rosenhek . Several studies have identified calcification of the aortic valve as an independent predictor of aortic regurgitation, the need for post-dilation, the need for pacemaker implantation, and the risk of annulus rupture in patients undergoing TAVR 1,2,[7][8][9][10]15,16 . While these findings are well established for the overall extent of valve calcification, little is known about the spatial distribution of calcifications within the different levels of the aortic root, including Overall calcification grade Prevalence of moderate/severe AR Overall calcification grade Prevalence of moderate/severe AR …”
Section: Discussionmentioning
confidence: 99%
“…Rosenhek . Several studies have identified calcification of the aortic valve as an independent predictor of aortic regurgitation, the need for post-dilation, the need for pacemaker implantation, and the risk of annulus rupture in patients undergoing TAVR 1,2,[7][8][9][10]15,16 . While these findings are well established for the overall extent of valve calcification, little is known about the spatial distribution of calcifications within the different levels of the aortic root, including Overall calcification grade Prevalence of moderate/severe AR Overall calcification grade Prevalence of moderate/severe AR …”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with the underlying hypothesis that specific approach-related parameters might outperform a rather global risk categorization in terms of outcome prediction after TA-TAVI. Besides the LVOT-aorta angle, obviously representing a key anatomic parameter in TA procedures, for example the calcification of the device landing zone has been shown to predict unfavorable procedural outcome in terms of paravalvular leak [16] and postoperative pacemaker dependency [17]. Similarly, the total aortic calcification burden has been recently described as an integrative predictor of mortality after TAVI [8].…”
Section: Discussionmentioning
confidence: 99%
“…(55,57) Whether aortic root calcification is associated with pacemaker requirement is controversial. (58,59) Iatrogenic membranous VSD Iatrogenic membranous VSD is uncommon after TAVI but may have adverse consequences. (41,60) A case report described the occurrence of iatrogenic VSD following post-dilatation of the TAVI prosthesis with a relatively oversized balloon in a patient with an unusually long ventricular membranous septum.…”
Section: Device Dislodgementmentioning
confidence: 99%